Alternativas para el trabajo social de empresa - Rodríguez Conejero, Elena (Miscelánea Comillas, 2010)
Occupational Social Work is probably one of the lesser known areas inour profession. From its inception until now, it has been continuously adapting to changes in both the professional world and social care services. In the process, many hardworking professionals have been lost as they have been working in the shadows or dealing with a profit-centered model where human resources were not sufficiently taken care of. Nowadays, the relation between the workers’well being and their performance is recognized at last. The social worker has arole in combining the individual, social and contextual factors taking part in theme asure of productivity of the worker and the overall organization. The objectiveis to improve organizations, making them more successful and socially involved,a true Social Corporate Responsibility. Now it is time to take over this importantrole in organizations and to prove our job’s profitability.